Do Mission Statements Matter for Nonprofit Performance?: Insights from a Study of US Performing Arts Organizations. Issue 3 (20th January 2017) - Pandey, Sheela; Kim, Mirae; Pandey, Sanjay K.
Abstract : In this exploratory study, we examine whether organizational mission statement attributes make a difference to the performance of nonprofit performing arts organizations. We use text analysis to measure two semantic attributes—activity and commonality—of mission statements. We examine whether these attributes are associated with improved performance for the instrumental and expressive functions of nonprofit performing arts organizations. Our findings indicate that the mission statement attribute activity is associated with improved performance for both instrumental and expressive functions. Our analysis of nonfindings for the mission statement attribute commonality suggests that there is a need to develop and use content analysis tools tailored to nonprofit contexts.